A Missense Mutation in the Zinc Finger Domain of OsCESA7 Deleteriously Affects Cellulose Biosynthesis and Plant Growth in Rice - Wang, Daofeng (PLoS One, 2016)
Rice is a model plant species for the study of cellulose biosynthesis. We isolated a mutant, S1-24, from ethyl methanesulfonate (EMS)-treated plants of the japonica rice cultivar, Nipponbare. The mutant exhibited brittle culms and other pleiotropic phenotypes such as dwarfism and partial sterility. The brittle culms resulted from reduced mechanical strength due to a defect in thickening of the sclerenchyma cell wall and reduced cellulose content in the culms of the S1-24 mutant. Map-based gene cloning and a complementation assay showed that phenotypes of the S1-24 mutant were caused by a recessive point mutation in the OsCESA7 gene, which encodes cellulose synthase A subunit 7. The missense mutation changed the highly conserved C40 to Y in the zinc finger domain. The OsCESA7 gene is expressed predominantly in the culm at the mature stage, particularly in mechanical tissues such as vascular bundles and sclerenchyma cells, consistent with the brittle phenotype in the culm. These results indicate that OsCESA7 plays an important role in cellulose biosynthesis and plant growth.